PHYSICAL FITNESS, SELF-PERCEPTION AND PHYSICAL ACTIVITY IN CHILDREN WITH DIFFERENT MOTOR COMPETENCE - Kjelsås, Vedul- Vigdis; Stensdotter, Ann-Katrin; Haga, Monika; Sigmundsson, Hermundur (European Journal of Adapted Physical Activity, 2015)
The aim of the study was to investigate if children at the age of 11 with total scores at or above 13.5 (lower motor competence) on Motor assessment Battery for Children (MABC) differ from children scoring below 13.5 (higher motor competence) in physical fitness, self-perception and physical activity. A total of 67 children completed the Test of Physical Fitness and Harter‟s Self-perception Profile for Children, and two questions concerning physical activity. Children with lower motor competence performed poorer on all fitness tasks, were less physically active and had lower perception of athletic competence and social acceptance, than the group with higher motor competence. These findings indicate that lower levels of motor competence may impact several health related variables in children. In this respect the importance of experience with the tasks measured are discussed. Additionally, the benefits of a mastery-oriented climate to promote physical activity in school, especially for children with lower motor competence, are emphasized.
Keywords: motor skills; motor difficulties; health; school; physical education